Allogeneic stem cell transplant provides durable response in peripheral T-cell lymphoma. (August 2019) - Modi, Dipenkumar; Surapaneni, Malini; Kim, Seongho; Ayash, Lois; Alavi, Asif; Ratanatharathorn, Voravit; Deol, Abhinav; Uberti, Joseph P.
Highlights: Allogeneic stem cell transplant is a viable treatment in peripheral T-cell lymphoma. Non-relapse mortality is substantial. A few patients attain a durable response indicating graft versus lymphoma effect. Patients with prior autologous transplant should be offered allogeneic transplant.